Assessment of Addiction Medicine Training in Family Medicine Residency Programs: A CERA Study - Tong, Sebastian (Fam Med, 2017)
BACKGROUND AND OBJECTIVES: Substance use disorder (SUD) is a wide-spread problem but physicians may feel inadequately prepared to provide addiction care. We sought to assess current addiction medicine curricula in US family medicine residencies (FMRs) and evaluate barriers to improving or implementing addiction medicine curricula. METHODS: Questions regarding addiction medicine training were added to the December 2015 Council of Academic Family Medicine Educational Research Alliance (CERA) survey to US FMR program directors to evaluate each FMR’s curriculum, potential workforce production, perceived barriers to improving or implementing curricula and faculty training in addiction medicine. RESULTS: Of 461 FMR directors, 227 (49.2%) responded; 28.6% reported a required addiction medicine curricula. Regional variations of having a required curriculum ranged from 41.3% in the Northeast to 20.0% in the South (P=0.07). Of residencies, 31.2% had at least one graduate obtain a buprenorphine prescription waiver in the past year and 8.6% had at least one graduate pursue an addiction medicine fellowship in the past 5 years. Lack of faculty expertise was the most commonly cited barrier to having a curriculum, with only 36.2% of programs having at least one buprenorphine waivered faculty member, 9.4% an addiction medicine board certified faculty, and 5.5% a fellowship trained faculty. CONCLUSIONS: Few FMRs have addiction medicine curricula and most graduates do not seek additional training. Multifaceted efforts, including developing model national curricula, training existing faculty, and recruiting addiction trained faculty, may improve addiction medicine training in family medicine residencies to better address the growing SUD epidemic.